2022
DOI: 10.1371/journal.pone.0272525
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the elderly’s behavioural intention to use smart home technologies in Saudi Arabia

Abstract: In recent years, smart home technologies have offered opportunities for elderly people to manage their daily health-related activities. Despite the advancement in smart home technology (SHT), the level of end-user acceptance among elderly people is still low. This study proposes an SHT framework by examining the determinants of elderly behavioural intention (BI) to use smart home technologies by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This study uses the quantitative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Several studies have examined the factors that influence the acceptance of smart home services by older adults, including personal and environmental perception factors. Personal perception factors comprise perceived ease of use, perceived usefulness, perceived cost ( 16 ), facilitating conditions ( 7 ),technology anxiety ( 17 ), and security and privacy concerns ( 16–18 ). Environmental perception factors include social influence ( 7 , 18 ), subjective norms ( 15 ), cultural influence ( 7 ), family management policies, and government policies ( 18 ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the factors that influence the acceptance of smart home services by older adults, including personal and environmental perception factors. Personal perception factors comprise perceived ease of use, perceived usefulness, perceived cost ( 16 ), facilitating conditions ( 7 ),technology anxiety ( 17 ), and security and privacy concerns ( 16–18 ). Environmental perception factors include social influence ( 7 , 18 ), subjective norms ( 15 ), cultural influence ( 7 ), family management policies, and government policies ( 18 ).…”
Section: Related Workmentioning
confidence: 99%
“…Numerous studies have shown that smart home services are beneficial to the well-being of the older adult ( 6 ). The benefits of smart home services include independent living, improved healthcare, social involvement, safety, cost reduction, and decision making ( 7 ). Therefore, smart home services can help maintain independence and improve the quality of life ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The highest used mediators in the context of IoT adoption are attitude with a frequency of 25, perceived usefulness (17 times), behavioral intention (13 times), and “perceived ease of use.” The other mediators are “perceived risk” (4 times), public value (3 times), trust (3 times), perceived value (3 times), facilitation appropriation (2 times), subjective norm (1 time), value co‐creation (1 time), information quality (1 time), system quality (1 time), motivation (1 time) and personal innovation (1 time). Nawi et al (2022) reported that attitude plays a mediating role between the “performance expectancy, facilitating conditions, perceived enjoyment, perceived trust, perceived risk” and “acceptance of IoT.” Similarly, Maswadi et al (2022) found a significant mediating role of attitude between “effort expectancy, performance expectancy” and “behavioral intention.” Chohan et al (2021) validated a mediating effect of public value between “information privacy value, digital society affinity, public trust value” and “continuous usage intention.” Also, they have found the partial mediation of public value between “social influence value, citizens’ empowerment value” and “continuous usage intention.”…”
Section: Content Analysismentioning
confidence: 99%
“…reported that attitude plays a mediating role between the "performance expectancy, facilitating conditions, perceived enjoyment, perceived trust, perceived risk" and "acceptance of IoT." Similarly,Maswadi et al (2022) found a significant mediating role of attitude between "effort expectancy, performance expectancy" and "behavioral intention. "Chohan et al (2021) validated a mediating effect of public value between "information privacy value, digital society affinity, public trust value" and "continuous usage intention."…”
mentioning
confidence: 95%
“…Few studies have looked at the question of IoTHD adoption in emerging nations like Saudi Arabia (Maswadi et al, 2022). The government is improving Saudi Arabia's infrastructure, while the elderly with chronic disease usage of technology is low.…”
Section: Introductionmentioning
confidence: 99%